2019
DOI: 10.1039/c9dt03564h
|View full text |Cite
|
Sign up to set email alerts
|

Supermetal: SbF5-mediated methane oxidation occurs by C–H activation and isobutane oxidation occurs by hydride transfer

Abstract: SbVF5 is generally assumed to oxidize methane through a methanium-to-methyl cation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Following our previous modeling of Hg II -mediated methane C–H functionalization in sulfuric acid, which showed excellent agreement with experimental rates and selectivity, we used DFT calculations combined with a continuum solvent implemented with sulfuric acid parameters. The B2PLYP-D3­(BJ)/ma-Def2-TZVPP//MN15/Def2-SVP Gibbs activation energy for methane C–H activation to give the resulting Sb V -Me structure has a barrier of 35 kcal/mol (Δ H ‡ = 27 kcal/mol, Figure ). Importantly, this barrier for methane is lower than the energy to lose H 2 from [CH 5 ] + generated by protonolysis of CH 4 in superacid, which is >40 kcal/mol. , This provided an initial prediction that it could be possible that C–H activation outcompetes superacid reaction pathways for functionalization of methane, even in very strong sulfuric acid (Figure ).…”
Section: Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Following our previous modeling of Hg II -mediated methane C–H functionalization in sulfuric acid, which showed excellent agreement with experimental rates and selectivity, we used DFT calculations combined with a continuum solvent implemented with sulfuric acid parameters. The B2PLYP-D3­(BJ)/ma-Def2-TZVPP//MN15/Def2-SVP Gibbs activation energy for methane C–H activation to give the resulting Sb V -Me structure has a barrier of 35 kcal/mol (Δ H ‡ = 27 kcal/mol, Figure ). Importantly, this barrier for methane is lower than the energy to lose H 2 from [CH 5 ] + generated by protonolysis of CH 4 in superacid, which is >40 kcal/mol. , This provided an initial prediction that it could be possible that C–H activation outcompetes superacid reaction pathways for functionalization of methane, even in very strong sulfuric acid (Figure ).…”
Section: Results and Discussionmentioning
confidence: 96%
“…Importantly, this barrier for methane is lower than the energy to lose H 2 from [CH 5 ] + generated by protonolysis of CH 4 in superacid, which is >40 kcal/mol. 38,39 This provided an initial prediction that it could be possible that C−H activation outcompetes superacid reaction pathways for functionalization of methane, even in very strong sulfuric acid (Figure 1). This initial calculation prompted us to simultaneously calculate pathways other than protonolysis (e.g., electron transfer and hydride abstraction) as well as experimentally examine the reaction between methane and Sb V in sulfuric acid.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No formaldehyde (HCHO) was observed from HPLC analysis, and no CO 2 was observed in the gas phase from GC analysis after 5 h reaction, suggesting that ∼100% CH 4 utilization efficiency was achieved without overoxidation. Overoxidation in the homogeneous system has been reported to be a serious issue because of the weaker C–H bond in CH 3 OH (96 kcal/mol) than that in CH 4 (104 kcal/mol). ,, While an indirect method by forming methyl esters as intermediate products was a useful strategy to protect the product from overoxidation due to the electron-withdrawing effect of the ester group in homogeneous catalytic oxidation of CH 4 in strongly acidic media, it is a remarkable advantage of the [Eim]­[NTf 2 ]/H 2 O 2 system discovered in this work to directly produce CH 3 OH and HCOOH by avoiding the need for strong acid to form an ester as the intermediate product. In addition to high CH 4 solubility in the hydrophobic [Eim]­[NTf 2 ], a two-phase system may be formed between [Eim]­[NTf 2 ] and H 2 O that was introduced as a bulk component of the 35 wt % H 2 O 2 solution.…”
Section: Resultsmentioning
confidence: 98%
“…The partial oxidation of CH 4 in homogeneous systems has attracted considerable interest since Shilov et al reported the direct conversion of CH 4 to CH 3 OH using Pt II as the C–H activation catalyst and Pt IV as the oxidant at 120 °C . Mechanistic studies and numerous efforts have been made to improve the efficiency of this “Shilov Chemistry”. A large number of works on selective CH 4 oxidation have been focused on metal complexes, including precious metals such as Pt II , Pd II , Au III/I , and Ir III and main-group metals such as Hg II , Sb V , In III , Sn IV , Ti II , and Pb IV in strongly acidic media . A landmark work by Periana et al showed the conversion of CH 4 to methyl bisulfate, (CH 3 )­HSO 4 , as a primary product that was subsequently worked up by hydrolysis to produce CH 3 OH.…”
Section: Introductionmentioning
confidence: 99%